Time history response analysis of a slender tower under translational-rocking seismic excitations. (15th January 2018) - Bońkowski, Piotr Adam; Zembaty, Zbigniew; Minch, Maciej Yan
Highlights: 6-dof, moderately intensive ground motion records are utilized in structural response analyses. Time history response numerical analysis of a high reinforced concrete industrial chimney is carried out. Results show substantial (18–65%) contribution of rotational excitation effects in seismic response. A unique interaction of rotational and horizontal ground excitations in overall structural response is indicated. Abstract: Two records from 6-dof ground motion monitoring of induced seismic events are applied to study seismic response of a slender tower under horizontal-rotational excitations. The response of 160 m reinforced concrete, industrial chimney is investigated under moderately intensive, simultaneously acting translational-horizontal and rocking components of the ground motion (rotation about horizontal axis). Time history response analysis shows substantial contribution of rotational excitations in the flexural vibrations of the chimney: 18% in the upper part and 65% at the base. The paper demonstrates that overall response of slender towers can effectively be studied only by using credible, 6-dof seismic records because of the important role of interaction of horizontal and rotational excitations, in which frequency contents and proper phases of excitation records play important role in the structural response. Results of such analyses with more and more intensive records are important for future calibrations of seismic design codes using response spectrum approach, as in the case of Eurocode 8, part 6: Towers, masts and chimneys .